Magnetic switching of nanoscale antidot lattices - Wiedwald, Ulf; Gräfe, Joachim; Lebecki, Kristof M.; Skripnik, Maxim; Haering, Felix; Schütz, Gisela; Ziemann, Paul; Goering, Eberhard; Nowak, Ulrich (Beilstein Journal of Nanotechnology, 2016)
We investigate the rich magnetic switching properties of nanoscale antidot lattices in the 200 nm regime. In-plane magnetized Fe, Co, and Permalloy (Py) as well as out-of-plane magnetized GdFe antidot films are prepared by a modified nanosphere lithography allowing for non-close packed voids in a magnetic film. We present a magnetometry protocol based on magneto-optical Kerr microscopy elucidating the switching modes using first-order reversal curves. The combination of various magnetometry and magnetic microscopy techniques as well as micromagnetic simulations delivers a thorough understanding of the switching modes. While part of the investigations has been published before, we summarize these results and add significant new insights in the magnetism of exchange-coupled antidot lattices.
Keywords: antidot lattice; first-order reversal curves; Kerr microscopy; magnetic nanostructures; magnetic switching; micromagnetic simulations; plasma etching; spin ice; X-ray microscopy